2002
DOI: 10.1128/mcb.22.4.1094-1105.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient for the Wild-Type p53-Induced Phosphatase Gene (Wip1) Exhibit Defects in Reproductive Organs, Immune Function, and Cell Cycle Control

Abstract: The Wip1 gene is a serine/threonine phosphatase that is induced in a p53-dependent manner by DNAdamaging agents. We show here that Wip1 message is expressed in moderate levels in all organs, but is present at very high levels in the testes, particularly in the postmeiotic round spermatid compartment of the seminiferous tubules. We have confirmed that Wip1 mRNA is induced by ionizing radiation in mouse tissues in a p53-dependent manner. To further determine the normal biological function of Wip1 in mammalian or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
192
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 166 publications
(206 citation statements)
references
References 22 publications
13
192
1
Order By: Relevance
“…Additional functions for PPM1D include the regulation of the base excision pathway of DNA repair (Lu et al, 2004), progesterone receptor function (Proia et al, 2006), the homoeostatic regulation of the checkpoint kinases CHK1 and CHK2 (Lu et al, 2005;Fujimoto et al, 2006;Nannenga et al, 2006;OlivaTrastoy et al, 2006;Yoda et al, 2006;Yu et al, 2006) and the activation of ataxia-telangiectasia mutated (Shreeram et al, 2006), all of which may also contribute to the oncogenic effects of PPM1D overexpression. Mice deficient in Ppm1d are viable, with only minor defects in immune function and spermatogenesis (Choi et al, 2002). However, these animals are resistant to mammary tumours induced by mouse mammary tumor virus-driven cHras1 or cNeu as well as to spontaneous tumour formation (Bulavin et al, 2004;Nannenga et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Additional functions for PPM1D include the regulation of the base excision pathway of DNA repair (Lu et al, 2004), progesterone receptor function (Proia et al, 2006), the homoeostatic regulation of the checkpoint kinases CHK1 and CHK2 (Lu et al, 2005;Fujimoto et al, 2006;Nannenga et al, 2006;OlivaTrastoy et al, 2006;Yoda et al, 2006;Yu et al, 2006) and the activation of ataxia-telangiectasia mutated (Shreeram et al, 2006), all of which may also contribute to the oncogenic effects of PPM1D overexpression. Mice deficient in Ppm1d are viable, with only minor defects in immune function and spermatogenesis (Choi et al, 2002). However, these animals are resistant to mammary tumours induced by mouse mammary tumor virus-driven cHras1 or cNeu as well as to spontaneous tumour formation (Bulavin et al, 2004;Nannenga et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it is of interest to note that fibroblasts from Wip1-null embryos exhibit a decreased proliferation rate. 36 It has been reported that Wip1 contributes to suppression of UVirradiation-induced apoptosis by dephosphorylating and inactivating p38. 24 However, g-irradiation-induced apoptosis of MCF7 cells transfected with Wip1 siRNAs was unaffected in the absence or presence of the specific inhibitor of p38, SB203580 (data not shown).…”
Section: Antagonistic Effect Of Wip1 On Chk2-dependent Apoptosismentioning
confidence: 99%
“…The mammalian PPM1D gene coding for the nuclear PP2C delta isoform (or Wip1) was originally identified by its p53-dependent transcriptional induction in response to ionizing IR (Fiscella et al, 1997) and was thus of particular interest for further study. Mice deficient for Wip1 exhibit defects in reproductive organ and immune function, and Wip1 À/À MEF cells have decreased proliferation rates owing to the activation of the p16 (Ink4a) and p19 (ARF) pathways (Choi et al, 2002;Bulavin et al, 2004). In response to genotoxic stress, Wip1 was recently shown to downregulate several checkpoint pathways.…”
Section: Introductionmentioning
confidence: 99%